2023
DOI: 10.1111/cen.14952
|View full text |Cite
|
Sign up to set email alerts
|

Men, testosterone and Covid‐19

Kristina Groti Antonic,
Blaz Antonic,
Monica Caliber
et al.

Abstract: Men have more severe Coronavirus disease 2019 (Covid‐19) outcomes and higher mortality rates than women, and it was suggested that testosterone levels might promote severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection and Covid‐19 severity. However, clinical studies have not supported this theory. Studies have consistently shown that serum testosterone concentrations during acute Covid‐19 in men are inversely proportional to the inflammatory cytokines and severity of illness. It is likely tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…We were interested in testosterone concentration because it has been shown that infection with the SARS-CoV-2 virus affects the production of this hormone. It has also been shown that testosterone levels influence the course of COVID-19 disease [54,55]. Toscano-Guerra et al [55] showed a significant role of testosterone status in the immune responses to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…We were interested in testosterone concentration because it has been shown that infection with the SARS-CoV-2 virus affects the production of this hormone. It has also been shown that testosterone levels influence the course of COVID-19 disease [54,55]. Toscano-Guerra et al [55] showed a significant role of testosterone status in the immune responses to COVID-19.…”
Section: Introductionmentioning
confidence: 99%